2023
DOI: 10.1039/d2tc05072b
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of the valence state of Ru metal ions in correlation with the structural and electronic properties of double perovskite ruthenates; A2SmRuO6 (where A = Ba & Sr)

Abstract: We report combined experimental and theoretical investigations for the oxidation states of Ru ions in the double perovskite ruthenates: Ba2SmRuO6 (BSRO) and Sr2SmRuO6 (SSRO). The Rietveld analysis of X-ray diffraction...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 53 publications
(75 reference statements)
1
4
0
Order By: Relevance
“…Figure 2 illustrates the fitted energy versus volume curves for double perovskites Ba 2 LnRuO 6 (Ln = Eu, Dy). Upon comparing our structural properties with other studies, it was observed that Ba 2 EuRuO 6 exhibits cubic symmetry through experimental methods [22] and Ba 2 DyRuO 6 [21,23] Ba 2 GdRuO 6 [26,50], Ba 2 SmRuO 6 [51], Ba 2 NdRuO 6 [29], and Ba 2 ErRuO 6 [29] were also favourably stabilized in cubic symmetry (Fm m 3 ). On the other hand, Ca 2 LnRuO 6 (Ln = Eu, Dy) [27,28], as well as Sr based structures like Sr 2 GdRuO 6 [26], Sr 2 SmRuO 6 [51] were reported to adopt monoclinic symmetry (P2 1 /n) due to size mismatch between A and B site cations.…”
Section: Structural Propertiessupporting
confidence: 58%
“…Figure 2 illustrates the fitted energy versus volume curves for double perovskites Ba 2 LnRuO 6 (Ln = Eu, Dy). Upon comparing our structural properties with other studies, it was observed that Ba 2 EuRuO 6 exhibits cubic symmetry through experimental methods [22] and Ba 2 DyRuO 6 [21,23] Ba 2 GdRuO 6 [26,50], Ba 2 SmRuO 6 [51], Ba 2 NdRuO 6 [29], and Ba 2 ErRuO 6 [29] were also favourably stabilized in cubic symmetry (Fm m 3 ). On the other hand, Ca 2 LnRuO 6 (Ln = Eu, Dy) [27,28], as well as Sr based structures like Sr 2 GdRuO 6 [26], Sr 2 SmRuO 6 [51] were reported to adopt monoclinic symmetry (P2 1 /n) due to size mismatch between A and B site cations.…”
Section: Structural Propertiessupporting
confidence: 58%
“…65,66 The observed results likely stem from the substitution of Ru, affecting the interaction between elements and indicating a mixed oxidation state of Ru n+ ions, including Ru 4+$ within the pyrochlore structure. [67][68][69] For oxygen binding energy shown in Fig. 4d, the lower binding energy peak at approximately 529 eV is attributable to lattice oxygen (O lat ), while the peak at around 531 eV is associated with adsorbed surface oxygen, OH groups, and oxygen vacancies (O ads ).…”
Section: C=o ¼ Mole Of C Inlet Fuels Mole Of O Of Inlet Fuels Exclude...mentioning
confidence: 99%
“…, especially at low temperatures. These DPs have been explored theoretically and experimentally by our research group 17,18 and a few other research groups for their intriguing structural, thermal, and high-temperature phase transition properties. 19 For example, polycrystalline double perovskites, Ba 2 GdRuO 6 & Sr 2 GdRuO 6 , show half-metallicity, which was confirmed via density functional theory (DFT) based calculations.…”
Section: Introductionmentioning
confidence: 99%
“…12 Among these rare-earth-based compounds, we are particularly interested in specific double perovskites (DPs), having general formula A 2 BRuO 6 (where A = Sr, Ba, Ca, and B = a rare earth ion) due to their fascinating properties such as metallic/ half-metallic nature, multiferroics, colossal magnetoresistance (CMR), canted anti-ferromagnetism, [13][14][15][16] etc., especially at low temperatures. These DPs have been explored theoretically and experimentally by our research group 17,18 and a few other research groups for their intriguing structural, thermal, and high-temperature phase transition properties. 19 For example, polycrystalline double perovskites, Ba 2 GdRuO 6 & Sr 2 GdRuO 6 , show half-metallicity, which was confirmed via density functional theory (DFT) based calculations.…”
Section: Introductionmentioning
confidence: 99%